Pengembangan Media Pembelajaran Multimedia Interaktif dalam Materi Novel Berbasis Aplikasi Powtoon untuk Kelas XII SMAN I Panai Hilir - Lubis, Khairatunnisa; Andriany, Liesna; Ali, Ali (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2025)
This study aimed to develop and evaluate the feasibility of interactive multimedia learning media using the Powtoon application for novel material in Class XII at SMAN 1 Panai Hilir. The research employed a quantitative descriptive approach, with data collected through questionnaires. Respondents included material experts, media experts, and Class XII students. The research followed the ADDIE development model by Robert Maribe Branch (2009), which consists of five interrelated stages: analysis, design, development, implementation, and evaluation. Product validation was conducted by four experts—two material experts and two media experts. The validation results indicated that material expert I rated the product at 76.8% (categorized as feasible), while material expert II rated it at 77.5% (categorized as feasible). Meanwhile, media expert I provided a score of 93.33% (categorized as highly feasible), and media expert II gave a score of 97.33% (categorized as highly feasible). After revising the product based on expert feedback, student testing was conducted using a questionnaire. The media was tested in Classes XII RPL I and XII RPL II at SMAN 1 Panai Hilir. Student response data showed that Class XII RPL I scored 86.15%, and Class XII RPL II scored 85.72%, indicating that the learning media was valid and highly suitable for classroom use.